Academic Senate Minutes 2002-05-23 - Academic Senate:::::::::
Additional items added to the Agenda. Approval of minutes postponed. Report from Chair of the Faculty. The following consent items were approved: Biochemistry Concentration for Chemistry Major; Name Changes of Music Major Concentration; and 4 unit courses for English Major and M.A. Program. Revision Proposal from Department of Childhood and Elementary Education and Department of Reading, Language and Culture Program: Multiple Subject Professional Teacher Preparation Program approved. Revision Proposal from Department of Curriculum Studies and Secondary Education: Single Subject Teacher Preparation Program approved. Library report from Raye Lynn Thomas. Consolidation of Education Departments approved. Vacant lecturer seat approved for Marilyn Dudley-Rawley and issue of vacancies after elections but before taking office referred to Structures & Functions. FSAC's Ranking policy statement amended and approved. Reports from B. Goldstein, S. Hayes, J. Holian, APC, EPC, FSAC, SAC. Installation of new officers. Resolution for Rick Luttmann unanimously approved.